Copper‐Catalyzed Oxidative Amination and Allylic Amination of Alkenes. Issue 38 (22nd July 2013) - Liwosz, Timothy W.; Chemler, Sherry R.
Abstract Enamines and enamides are useful synthetic intermediates and common components of bioactive compounds. A new protocol for their direct synthesis by a net alkene CH amination and allylic amination by using catalytic CuII in the presence of MnO2 is reported. Reactions between N‐aryl sulfonamides and vinyl arenes furnish enamides, allylic amines, indoles, benzothiazine dioxides, and dibenzazepines directly and efficiently. Control experiments further showed that MnO2 alone can promote the reaction in the absence of a copper salt, albeit with lower efficiency. Mechanistic probes support the involvement of nitrogen‐radical intermediates. This method is ideal for the synthesis of enamides from 1, 1‐disubstituted vinyl arenes, which are uncommon substrates in existing oxidative amination protocols.